New frontiers and conceptual frameworks for energy justice. (June 2017) - Sovacool, Benjamin K.; Burke, Matthew; Baker, Lucy; Kotikalapudi, Chaitanya Kumar; Wlokas, Holle
Abstract: This article explores how concepts from justice and ethics can inform energy decision-making and highlight the moral and equity dimensions of energy production and use. It defines "energy justice" as a global energy system that fairly distributes both the benefits and burdens of energy services, and one that contributes to more representative and inclusive energy decision-making. The primary contribution of the article is its focus on six new frontiers of future energy justice research. First is making the case for the involvement of non-Western justice theorists. Second is expanding beyond humans to look at the Rights of Nature or non-anthropocentric notions of justice. Third is focusing on cross-scalar issues of justice such as embodied emissions. Fourth is identifying business models and the co-benefits of justice. Fifth is better understanding the tradeoffs within energy justice principles. Sixth is exposing unjust discourses. In doing so, the article presents an agenda constituted by 30 research questions as well as an amended conceptual framework consisting of ten principles. The article argues in favor of "justice-aware" energy planning and policymaking, and it hopes that its (reconsidered) energy justice conceptual framework offers a critical tool to inform decision-making. Highlights: We need "justice-aware" energy policy. A revised energy justice conceptual framework offers a critical tool to inform decision making. New fields of inquiry for energy justice research and practice exist. Tradeoffs and weighing competing justice claims occur in practice.